Enhancing the Prospective Acceptability of a Paediatric Speech and Language Therapy Intervention With Parents From Under‐Represented Communities - Lucy Rodgers; Nicola Botting; Ros Herman (Health Expectations, 2026)
ABSTRACT Background Integrating the perspectives of people with lived experience is integral to developing new healthcare interventions. However, individuals from under‐represented communities may face additional barriers to taking part in such patient and public involvement (PPI) activities. Within paediatric speech and language therapy (SLT), under‐represented communities might include families from lower SES backgrounds and/or families where the majority language for that country is not spoken. Excluding families from under‐represented communities poses the risk of new interventions not being acceptable to them, thus exacerbating pre‐existing healthcare inequalities. Objective The aim of this study was to optimise the prospective acceptability of a new paediatric speech and language therapy intervention with parents from under‐represented backgrounds, in the hope of optimising future accessibility to families from diverse communities. Methods An individualised PPI approach was taken, consisting of two semi structured interviews informed by the Theoretical Framework of Acceptability (TFA). Six parent partners from non‐majority language and/or lower SES backgrounds were recruited through a local charity. In the first interview, parent partners were shown a video of the intervention and identified key areas for increasing acceptability. Refinements were made to the intervention by the project steering group in an online meeting. These refinements were the topic of the second interview, where the impact on prospective acceptability was explored. Results Following the first round of interviews, areas for improvement included consideration of access to/co‐ordination with wider services, and the financial and practical implications for parents accessing the intervention. Most of the intervention refinements and solutions to potential barriers came directly from the parent partners themselves, rather than the steering group. In the second round of interviews, parent partners rated the intervention's prospective acceptability between 4/5 (acceptable) and 5/5 (very acceptable). Conclusion By working with parent partners from under‐represented communities, the research team was able to enhance the prospective acceptability of a new paediatric speech and language therapy intervention. Many refinements related to the wider healthcare and support system, rather than to the content of the intervention itself. This reinforces the importance of exploring and addressing wider contextual barriers within the intervention development process. Patient or Public Contribution The methods for this project were co‐designed with a project steering group consisting of 3 Speech and Language Therapists (one with specialist EDI expertise), a bi/multilingual education support worker, a specialist early years teacher, a parent of a child with developmental language disorder (DLD) and an adult with DLD. The steering group also assisted with identifying potential intervention refinements. The parent partners were responsible for identifying areas where acceptability could be increased and addressing the prospective acceptability of the intervention refinements.